Effect of Static Magnetic and Pulsated Electromagnetic Fields On the Dynamic and Kinematic Viscosity of Metal Cutting Fluids - Mardonov, Umidjon; Meliboyev, Yahyojon; Shaozimova, Umida Shaozimova (International Journal of Integrated Engineering, 2023)
In this paper, authors investigated the difference between the influence of permanent magnetic field and pulsating electromagnetic field on cutting fluids. Two essential physical parameters of the cutting fluids, dynamic and kinematic viscosity coefficients were measured during the experiment in the same laboratory condition. The results obtained from the experiments show that there is a noticeable difference between the impact of permanent magnetic field and pulsating electromagnetic field on cutting fluids. Three different types of fluids studied in the paper and these fluids are the most popular lubricating cooling fluids used in cutting process in manufacturing. All the experiments conducted in the same laboratory condition with the magnetic field strength of 40mT, 60mT and 80mT.